Keterkaitan Perilaku dengan Status Kebersihan Gigi Mulut Pada Siswa Tunagrahita di Sekolah Luar Biasa - Jumriani; Asriawal; Liasari, Ira; Khaera, Muftih; Priyambodo, Ardian (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2024)
Children with intellectual disabilities, known as mentally handicapped children, have physical and emotional disorders that distinguish them from typical children. Oral hygiene among intellectually disabled children tends to be lower compared to children without disabilities. This is due to their condition of below-average intelligence and difficulties in adapting adaptively, which affects their oral health maintenance behavior. Oral health maintenance behavior is one of the factors that can influence oral hygiene. This research aims to determine the relationship between oral health maintenance behavior and oral hygiene in intellectually disabled children at SLB Negeri 1 Makassar. This study is a quantitative research using an observational approach with a cross-sectional design. The sampling technique in this study used purposive sampling, resulting in a sample of 30 individuals who were then assessed for oral hygiene levels using the OHI-S and oral health maintenance behavior using a questionnaire. Data analysis used the Mann-Whitney test to determine differences between the two variables based on gender and Spearman correlation to determine the relationship between the variables. The results of the study showed that oral health maintenance behavior in female students is better than in male students, and the OHI-S scores of female students are better than those of male students. However, the significant difference was only in the behavior variable. Overall, there is a significant relationship between behavior and OHI-S in intellectually disabled children at SLB Negeri 1 Makassar.